Internal communication on the quality of administrative management in the II.EE. of the secondary level of the network 09 of Puente Piedra-Lima -2014 - Ibarra Alva, Américo (2022)
The scientific research has as its title the internal communication in the quality of the administrative management in the II.EE. Of the secondary level of the RED 09 of Puente Piedra. The population consisted of 150 teachers and the sample is 75 teachers, the design of the research is descriptive, correlational causal, cross-sectional. For the data collection, two structured questionnaires were made as a measurement and the instruments comply with the validity and reliability qualities. In the research structure it includes the first chapter, the problem statement, the formulation of the problem, the objectives, the justification, the hypothesis, the identification and classification of variables. The second, presents background, theoretical basis and basic terms and the third, addresses the operationalization of variables, typing, strategies, population and data collection instruments. The fourth has a process of contracting hypotheses, presentation, analysis and interpretation of data and hypothesis testing and ends with conclusions, recommendations, bibliography and annexes. The results obtained allow us to reach the following conclusion, according to the Ch2 test the result of Correlation shows with an index of 0.953, that is 95.3%, with a freedom index of, 047 or 4.7%, with which The alternative hypothesis is validated: "Internal communication is related to the quality of administrative management in II.EE. Of The Secondary Level Of RED 09 Of Puente Piedra-Lima -2014 ".